2000
DOI: 10.1024/1023-9332.6.6.328
|View full text |Cite
|
Sign up to set email alerts
|

Fulkerson's Modified Elmslie-Trillat Procedure for Objective Patellar Instability and Patellofemoral Pain Syndrome

Abstract: Twenty two knees were either operated for objective patellar instability (Group A: 14 patients) or patellofemoral pain syndrome (Group B: 8 patients) using Fulkerson's modified Elmslie-Trillat procedure. The objective of this retrospective study was to evaluate the results of this method and to detect whether or not there were differences in the outcome comparing the two groups. Twenty knee joints (Group A: 13; group B: 7) were available for clinical and radiographic examination after an overall mean follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Rillman et al [128] have proposed a Fulkerson's modified Elmslie-Trillat procedure for objective patellar instability and patellofemoral pain syndrome. Based on their results authors have concluded that the operation is an excellent treatment method with a very low morbidity for patients with patellofemoral malalignment after failed conservative treatment.…”
Section: Distal Realignment Proceduresmentioning
confidence: 99%
“…Rillman et al [128] have proposed a Fulkerson's modified Elmslie-Trillat procedure for objective patellar instability and patellofemoral pain syndrome. Based on their results authors have concluded that the operation is an excellent treatment method with a very low morbidity for patients with patellofemoral malalignment after failed conservative treatment.…”
Section: Distal Realignment Proceduresmentioning
confidence: 99%
“…Some prior studies 4, 34, 47 observed excellent patient reported outcomes following TT osteotomy for individuals with intractable PFP and no history of patellar dislocation. However, other studies 24, 30 reported only fair results in this population with a less favorable prognosis compared to individuals with a history of patellar dislocation.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, no recommendation exists for the TT-TG distance that should prompt consideration for TT osteotomy in patients with intractable PFP; yet, this surgical procedure is frequently performed after failed nonoperative treatment. 4,16,18,19,24,34,47 Prior studies 3,8,46 assigned a pathological threshold of 15 mm for TT-TG distances when measured using MRI for patients with a history of patellar dislocations. This value is approximately 1.5 SDs above the observed control mean, and 30% of knees with isolated PFP demonstrated TT-TG distances at or above this value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 20, 26 Using the static distance between the TT and the trochlear groove (TT-TG) for pre-operative screening, TT osteotomy has been shown to yield excellent results for patients with a history of patellar dislocation. 46 While some studies 18, 24, 35, 46 investigating TT osteotomy for patients with intractable PFP, without a history of patellar dislocation, have also observed positive outcomes, other studies 12, 30, 37 have reported medial patellar instability, surgical failure, and a less favorable prognosis compared to cohorts with a history of patellar dislocation.…”
Section: Introductionmentioning
confidence: 99%